060 Intramuscular Testosterone Cypionate vs Subcutaneous Testosterone Enanthate: Comparing the Outcomes in Hypogonadal Men. (1st May 2022) - Choi, E.; Xu, P.; Loeb, C.; El-Khatib, F.; Yafi, F.; Kavoussi, P.
ABSTRACT: Introduction: Intramuscular testosterone cypionate (IM-TC) is the conventional treatment option for hypogonadal men with baseline serum total testosterone (TT) less than 300 ng/dL; however, significant peaks in testosterone cause adverse effects including polycythemia and rise in estradiol (E2). Subcutaneous testosterone enanthate-autoinjectors (SCTE-AI) were designed with a lower testosterone peak-to-trough ratio of 1.8. Objective: This dual-institutional study compared the TT, hematocrit (HCT), E2, and prostate-specific antigen (PSA) response to treatment with IM-TC versus SCTE-AI. Methods: 263 hypogonadal men were treated with testosterone replacement therapy (TRT) via IM-TC or SCTE-AI. TT, HCT, E2, and PSA levels were obtained at baseline and 6- to 12-weeks post-treatment. Significant differences in baseline and post-treatment levels were identified by univariate analysis. Linear regression models determined whether treatment modality was independently associated with post-TRT levels of TT, HCT, E2, and PSA. Results: Patients treated with SCTE-AI were significantly younger, had higher baseline TT levels, and lower baseline E2 levels (Table 1 ). Post-TRT, the SCTE-AI cohort had significantly lower HCT and E2, while TT and PSA levels were not significantly different between the treatment arms. After adjusting for significant differences with linear regression, SCTE-AI was associated with a 14% greater increase in trough TT levels compared to IM-TC ( p =0.027) (Table 2a ). Furthermore, SCTE-AI was independently associated with 41% and 26.5% lower post-therapy HCT (p<0.001) and E2 (p<0.001) levels, respectively, when compared to IM-TC (Table 2b -c ). Neither TRT modality was associated with post-therapy elevation of PSA (p=0.691). TT: Total Testosterone; HCT: Hematocrit; E2: Estradiol; PSA: prostate-specific antigen Conclusions: While IM-TC and SCTE-AI provide a significant increase in testosterone, SCTE-AI is associated with lower levels of post-therapy HCT and E2 compared to IM-TC after adjusting for significant covariates. SCTE-AI is an effective testosterone delivery system with a preferable safety profile over IM-TC. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (Antares Pharma, Clarus Therapeutics, Coloplast, Promescent, Viome).